Correlation of mineral status with levels of blood pressure in essential hypertension among patients attending a tertiary care hospital in South-India - Parisa Madhu Babu; M. Vasanthan; J. S. Kumar; V. M. Vinodhini; Renuka. P (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Essential or primary hypertension is considered to be the major reason of the complex interplay associated with several regulatory systems. It leads to main risk factors of cerebrovascular diseases, heart diseases, kidney malfunctioning. Essential hypertension is a chronic increase in blood pressure in the artery walls above 140 mm SBP and 90 mm DBP. It has a direct effect on the kidney, heart vessel by controlling the functions of endothelial layers and the RAAS mechanism by the kidney. The study designed to assess mineral status among patients with essential hypertension. 37 essential hypertension patient (25-50 years) & 37 normal control subject of same age and sex participated in the study. Serum level of different electrolytes & minerals were compared in both the groups. Serum sodium & calcium were significantly higher in patients with essential hypertension when compared to control group. A significant positive correlation of systolic blood pressure with serum potassium were observed. The correlation between sodium, iron, phosphorus and calcium was negative, while the correlation between magnesium and chloride was not significant. It was also evident that male gender is more likely to develop hypertension then females. It is seen that calcium and sodium levels are increased among essential hypertension patients and therefore exist a significant positive correlation between blood pressure with phosphorus levels. Therefore, patients diagnosed with essential hypertension must be regularly monitored for electrolytes and minerals levels to prevent further complications as a result of hypertension.